Ozone pollution will compromise efforts to increase global wheat production. (16th May 2018) - Mills, Gina; Sharps, Katrina; Simpson, David; Pleijel, Håkan; Broberg, Malin; Uddling, Johan; Jaramillo, Fernando; Davies, William J; Dentener, Frank; Van den Berg, Maurits; Agrawal, Madhoolika; Agrawal, Shahibhushan B.; et al.
Abstract: Introduction of high‐performing crop cultivars and crop/soil water management practices that increase the stomatal uptake of carbon dioxide and photosynthesis will be instrumental in realizing the United Nations Sustainable Development Goal (SDG) of achieving food security. To date, however, global assessments of how to increase crop yield have failed to consider the negative effects of tropospheric ozone, a gaseous pollutant that enters the leaf stomatal pores of plants along with carbon dioxide, and is increasing in concentration globally, particularly in rapidly developing countries. Earlier studies have simply estimated that the largest effects are in the areas with the highest ozone concentrations. Using a modelling method that accounts for the effects of soil moisture deficit and meteorological factors on the stomatal uptake of ozone, we show for the first time that ozone impacts on wheat yield are particularly large in humid rain‐fed and irrigated areas of major wheat‐producing countries (e.g. United States, France, India, China and Russia). Averaged over 2010–2012, we estimate that ozone reduces wheat yields by a mean 9.9% in the northern hemisphere and 6.2% in the southern hemisphere, corresponding to some 85 Tg (million tonnes) of lost grain. Total production losses in developing countries receiving Official Development Assistance are 50% higher than those in developed countries, potentially reducing the possibility of achieving UN SDG2. Crucially, our analysis shows that ozone could reduce the potential yield benefits of increasing irrigation usage in response to climate change because added irrigation increases the uptake and subsequent negative effects of the pollutant. We show that mitigation of air pollution in a changing climate could play a vital role in achieving the above‐mentioned UN SDG, while also contributing to other SDGs related to human health and well‐being, ecosystems and climate change. Abstract : Using a modelling method that accounts for the effects of soil moisture deficit and meteorological factors on the stomatal uptake of ozone pollution, we show that ozone impacts on wheat yield are particularly large in humid rain‐fed and irrigated areas of major wheat‐producing countries. Total production losses in developing countries receiving Official Development Assistance are 50% higher than those in developed countries, potentially reducing the possibility of achieving UN Sustainable Development Goal 2. Crucially, we show that ozone could reduce the potential yield benefits of increasing irrigation usage in response to climate change, by increasing stomatal uptake of the pollutant.